Effects of Baby Carrier on Wearer’s Posture Stability / Aizreena Azaman...[et al.] - Azaman, Aizreena; Mat Isa, Nurshazni Aiman; Mat Dzahir, Mohd Azuwan; Khor, Kang Xiang (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Design of baby carrier mostly focused on baby’s needs. But less consideration have been given to wearer. The objective of this study is to investigate the effect of baby carrier on the wearer’s posture stability and displacement. It was hypothesized that baby carrier would reduce loading effect caused by baby’s weight on the wearer’s body. Fifteen healthy young female volunteered to participate in this study. Three dimensional motion data and force distribution were collected using 3D Investigator system and force platform respectively. Subjects underwent three conditions of standing which are standing on the force plate without load (Control), standing on the force plate with load only (L) and standing on the force plate with load and wearing a baby carrier (LBC). In this study, dummy baby was used to create load effect mimicking real baby’s weight. For every condition, active markers will be placed at the subject’s joint and the subject is asked to standing quietly on the force plate. Then, effect of different position of baby carrier also will be analysed including front position, back position, and side position. In this investigation wrapping type of baby carrier or Mei Tai is used. Collected data were used to measure Centre of Pressure (COP) and joint displacement. The results shows that by using baby carrier there are significance change in shoulder and pelvic joint displacement. Baby carrier also reduced the COP sway compared to other condition, but no significance changes recorded. Even though changes in posture displacement and the COP sway were relatively small, further study is still warranted to improve function and comfort design of baby carrier.